2017
DOI: 10.3892/etm.2017.4771
|View full text |Cite
|
Sign up to set email alerts
|

Psoralen stimulates osteoblast proliferation through the activation of nuclear factor-κB-mitogen-activated protein kinase signaling

Abstract: Abstract. Osteoporosis is a systemic skeletal disease that leads to increased bone fragility and susceptibility to fracture. Approximately 50% of postmenopausal women develop osteoporosis as a result of postmenopausal estrogen deficiency. To reduce fractures related to osteoporosis in women, previous studies have focused on therapeutic strategies that aim to increase bone formation or decrease bone resorption. However, pharmacological agents that aim to improve bone fracture susceptibility exhibit side effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 52 publications
1
23
0
Order By: Relevance
“…Psoralen is extracted from the fruits of Psoralea corylifolia L . It has been reported to have antioxidant, antibacterial, antidepressant, antitumor, antidiabetic, and estrogen‐like activities (24, 25). Previous studies have demonstrated that psoralen inhibits metastasis of breast cancer to bone in vivo and promotes the formation of new bone mixed with collagen matrix in vivo (26, 27).…”
mentioning
confidence: 99%
“…Psoralen is extracted from the fruits of Psoralea corylifolia L . It has been reported to have antioxidant, antibacterial, antidepressant, antitumor, antidiabetic, and estrogen‐like activities (24, 25). Previous studies have demonstrated that psoralen inhibits metastasis of breast cancer to bone in vivo and promotes the formation of new bone mixed with collagen matrix in vivo (26, 27).…”
mentioning
confidence: 99%
“…However, the effect of psoralen on the phosphorylation of ASK1, JNK, and MAPK P38 in osteoblasts and osteoclasts remains controversial and requires further study (Li F. et al, 2017;Chen et al, 2017a;Chai et al, 2018;Zhang et al, 2019).…”
Section: Clinical Researchmentioning
confidence: 99%
“…Alkaline phosphatase (ALP) is a calcium-binding transporter located in the cell membrane which promotes cell maturation and calcification. Studies have demonstrated that psoralen increases the gene expression levels of osteoblast-specific markers such as GLUT3, Runx2, Col-I, osteocalcin, bone sialoprotein, and osterix, in addition to enhancing the activity of ALP, increasing colony formation in fibroblasts and promoting osteoblast differentiation ( Tang et al, 2011 ; Yang et al, 2012 ; Li F. et al, 2017 ; Zhang et al, 2019 ).…”
Section: Anti-osteoporotic Effects Of Psoralenmentioning
confidence: 99%
“…Bakuchiol has a three-fold higher binding affinity for estrogen receptor alpha (ERα) than for estrogen receptor beta (ERβ) [ 13 , 27 ]. It does not have significant uterotrophic activity, although demonstrating in vitro estrogenic activity [ 27 , 45 ]. It can reduce postmenopausal bone loss by increasing ALP, calcium concentrations, serum estrogen concentration, and bone mineral density [ 27 , 45 ].…”
Section: Antiosteoporotic Constituents Extracted From Natural Planmentioning
confidence: 99%
“…It does not have significant uterotrophic activity, although demonstrating in vitro estrogenic activity [ 27 , 45 ]. It can reduce postmenopausal bone loss by increasing ALP, calcium concentrations, serum estrogen concentration, and bone mineral density [ 27 , 45 ]. Psoralen, a coumarin-like derivative extracted from the fruit of P. corylifolia L., has stimulatory effects on new bone formation [ 27 , 46 , 47 ].…”
Section: Antiosteoporotic Constituents Extracted From Natural Planmentioning
confidence: 99%